Metabolism of Methoxychlor by the P450-Monooxygenase CYP6G1 Involved in Insecticide Resistance of Drosophila melanogaster after Expression in Cell Cultures of Nicotiana tabacum. - Joußen, N.; Schuphan, I.; Schmidt, B. (Chemistry & Biodiversity, 2010)
Cytochrome P450 monooxygenase CYP6G1 of Drosophila melanogaster was heterologously expressed in a cell suspension culture of Nicotiana tabacum. This in vitro system was used to study the capability of CYP6G1 to metabolize the insecticide methoxychlor (=1,1,1-trichloro-2,2-bis(4-methoxyphenyl)ethane, 1) against the background of endogenous enzymes of the corresponding non-transgenic culture. The Cyp6g1-transgenic cell culture metabolized 96% of applied methoxychlor (45.8 microg per assay) within 24 h by demethylation and hydroxylation mainly to trishydroxy and catechol methoxychlor (16 and 17%, resp.). About 34% of the metabolism and the distinct formation of trishydroxy and catechol methoxychlor were due to foreign enzyme CYP6G1. Furthermore, methoxychlor metabolism was inhibited by 43% after simultaneous addition of piperonyl butoxide (458 microg), whereas inhibition in the non-transgenic culture amounted to 92%. Additionally, the rate of glycosylation was reduced in both cultures. These results were supported by the inhibition of the metabolism of the insecticide imidacloprid (6; 20 microg, 24 h) in the Cyp6g1-transgenic culture by 82% in the presence of piperonyl butoxide (200 microg). Due to CYP6G1 being responsible for imidacloprid resistance of Drosophila or being involved in DDT resistance, it is likely that CYP6G1 conveys resistance to methoxychlor (1). Furthermore, treating Drosophila with piperonyl butoxide could weaken the observed resistance phenomena.